ANALYSIS OF KNOWLEDGE OF HEALTH FACULTY STUDENTS ABOUT PAIN MANAGEMENT USING THE TUINA METHOD - harditya, kadek buja; Komang Rosa Tri Anggaraeni; Luh Gede Nita Sri Wahyuningsih (Sean Institute, 2022)
Acute pain is generally related to the body's response to a health problem such as the presence of comorbidities, inflammatory processes or the psychological perception of an injury. Pain response can be modified in intensity by using drugs or other complementary therapies such as tuina. Tuina is a therapeutic technique originating from China by using pressure or massage techniques at the location of certain points on the body to reduce pain. Continuous pain management studies are important for the development of health sciences so that they can increase health students' knowledge regarding the management of pain problems. Purpose: This study aims to describe the knowledge of Health Faculty students at ITEKES Bali about pain management using the tuina method. Research Methods: Quantitative research with descriptive analysis method was used on 300 respondents by purposive sampling technique. Results: Health Faculty students' knowledge of pain management with the tuina method was in the good category (30.3%), sufficient category (48.7%) and poor category (21.0%). Conclusion: By knowing the description of student knowledge, it becomes a motivation in introducing and developing knowledge of the Tuina method of pain management so that it can be learned, applied or practiced by health workers or students.